Inequality and the business cycle: Evidence from U.S. survey data - Martin Geiger; Eric Mayer; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We study the effects of macroeconomic shocks on several measures of economic inequality obtained from U.S. survey data. To identify aggregate supply, aggregate demand, and monetary policy shocks, we estimate structural vector autoregressions and impose sign and zero restrictions on impulse response functions. Our results show that the effects of the macroeconomic shocks on economic inequality depend on the type of shock as well as on the measure of inequality considered. Contractionary monetary policy shocks increase expenditure and consumption inequality, whereas income and earnings inequality are less affected. Adverse aggregate supply and aggregate demand shocks increase income and earnings inequality, but reduce expenditure and consumption inequality. Our results suggest that different channels dominate in the transmission of the shocks. The earnings heterogeneity channel is consistent with the inequality dynamics in the aftermath of monetary policy shocks, but it appears to be less crucial when the economy is hit by either aggregate supply or aggregate demand shocks. In the aftermath of aggregate supply and aggregate demand shocks, inflation and the real interest rate appear to drive inequality dynamics to a larger degree. Using variance decompositions, we also find that although the macroeconomic shocks account for large shares of the variation in the macroeconomic variables, their contributions to the dynamics of the inequality measures are limited.
Keywords: E00; E32; D63; 330; Macroeconomic Shocks; Inequality; Structural Vector Autoregression; Zero and Sign Restrictions